2011
DOI: 10.1063/1.3597826
|View full text |Cite
|
Sign up to set email alerts
|

Electron-impact excitation cross sections into Ne(2p53p) levels for plasma applications

Abstract: One requirement for plasma spectroscopy analysis and modeling of neon discharges is a set of electron-impact excitation cross sections covering excitation from both the 2p6 ground state and from the four 2p53s levels. We present experimental measurements for excitation cross sections into four J = 1 levels of the 2p53p configuration from the J = 0 and J = 2 2p53s metastable levels. A complete set of cross sections into all ten levels of the 2p53p configuration (2px in Paschen’s notation) from the ground state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The depopulation of 2p i levels was assumed through radiative decay to 1s i manifolds. The apparent crosssection measurements [40,43,45] were used for inclusion of the collisional processes in the model of Boffard et al [48,67]. The T e obtained by the emission model at 5 mTorr pressure is ∼10.4 eV, which is significantly higher than the corresponding probe measurement and the present CR model values.…”
Section: Plasma Diagnostic Results and Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The depopulation of 2p i levels was assumed through radiative decay to 1s i manifolds. The apparent crosssection measurements [40,43,45] were used for inclusion of the collisional processes in the model of Boffard et al [48,67]. The T e obtained by the emission model at 5 mTorr pressure is ∼10.4 eV, which is significantly higher than the corresponding probe measurement and the present CR model values.…”
Section: Plasma Diagnostic Results and Discussionmentioning
confidence: 60%
“…Later Zatsarinny et al [39] also compared their BSR calculations with them. Jung et al [45] further reported the remaining cross-sections from 1s 5 and 1s 3 to 2p i levels with J=1 (where i=2, 5, 7, and 10) for a limited electron energy range from threshold to ∼16 eV. But again, these cross-sections are apparent cross-sections, and consist of cascades from other higher levels; consequently, these are not being compared here.…”
Section: Eie Cross-sectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In such a case, the electrons are at higher temperature than the ionic and neutral species. The temperatures of ions and neutrals usually take lower values close to that of the ambient environment, that is, from room temperature up to 1000 K, whereas the electrons can feature temperatures above 10,000 K. The energy is transferred between the discharge and the atoms or molecules through electron impact . It is commonly responsible for the well‐known process of dissociation that leads to the breaking of molecular bonds and the generation of chemical products during the chemical reactions.…”
Section: Energy‐based Methods For Orienting and Activating Molecules:mentioning
confidence: 99%